What you need to know to drill a high pressure, high temperature well. Issue 1 (1st December 2019) - Slade, Jonathan
Summary: The challenges in drilling a high pressure and high temperature (HPHT) well are unique to every opportunity. The key to successfully drilling an HPHT well is to utilise the appropriate people, technology and design at the appropriate time. To do this it is critical to know the questions that need solving. Knowing and answering these questions cannot be effectively achieved without accessing subject matter experts in several disciplines including drilling, petrophysics and data acquisition and integrating into a coherent plan.